Pengaruh Penerapan Asas Praduga Tak Bersalah terhadap Perlindungan Hak Tersangka dalam Proses Penyidikan - Muhammad Ghifari Satria Negara; Ilham Pratama; Aufa Kamula (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
The presumption of innocence is a fundamental principle in criminal procedural law, affirming that every person suspected, arrested, detained, or prosecuted must be considered innocent until proven guilty by a court decision with permanent legal force. This research arises from the frequent violations of this principle in investigative practices, such as the use of excessive force by law enforcement, premature determination of suspects, and biased media coverage that portrays suspects as guilty before trial. The legal issue examined in this study concerns the extent to which the application of the presumption of innocence affects the protection of suspects’ rights during the investigation process, as well as how the principle is implemented in Indonesia’s law enforcement system. Based on this issue, three main problems are formulated the concept and legal basis of the presumption of innocence in Indonesian criminal procedure law, the influence of this principle on the protection of suspects’ rights during investigation, the inhibiting factors in its implementation in practice. This research employs a normative juridical method with statutory, conceptual, and case approaches. Data were obtained through literature studies on legal instruments such as the Indonesian Criminal Procedure Code (KUHAP), Law Number 48 of 2009 on Judicial Power, relevant literature, and court decisions. The results show that the implementation of the presumption of innocence significantly influences the protection of suspects’ rights, particularly in ensuring the right to personal liberty, the right to legal counsel, and the right not to be tortured or treated inhumanely during the investigation process. However, the implementation has not been optimal due to weak supervision, low awareness of human rights principles among law enforcement officers, and the influence of public opinion and the media. Therefore, consistent enforcement of the principle, improved professionalism of law enforcement, and the imposition of sanctions for violations are needed to ensure the realization of legal protection for suspects